2003
DOI: 10.1016/s0006-3495(03)75102-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of a Dipalmitoylphosphatidylcholine Bilayer with NaCl

Abstract: Molecular dynamics simulations are performed on two hydrated dipalmitoylphosphatidylcholine bilayer systems: one with pure water and one with added NaCl. Due to the rugged nature of the membrane/electrolyte interface, ion binding to the membrane surface is characterized by the loss of ion hydration. Using this structural characterization, binding of Na(+) and Cl(-) ions to the membrane is observed, although the binding of Cl(-) is seen to be slightly weaker than that of Na(+). Dehydration is seen to occur to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

67
297
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(366 citation statements)
references
References 32 publications
67
297
1
1
Order By: Relevance
“…For all considered POPC bilayers we computed the electrostatic potential from the Poisson equation by twice integrating over charge densities, see Figure 5 (top). For a salt-free POPC membrane we found that the overall potential difference between the membrane center and the aqueous phase is ∼0.55 V. This value is in agreement with numerous computational studies, 6,12,15,21,27,47,48 while corresponding experimental values are in the range of 200-600 mV. [49][50][51][52][53] Addition of NaCl leads to a pronounced change in the electrostatic potential of a PC membrane: The peak of the potential in the region of the lipidwater interface increases and is shifted toward the water phase, reflecting most likely a considerable reorientation of head group dipoles.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…For all considered POPC bilayers we computed the electrostatic potential from the Poisson equation by twice integrating over charge densities, see Figure 5 (top). For a salt-free POPC membrane we found that the overall potential difference between the membrane center and the aqueous phase is ∼0.55 V. This value is in agreement with numerous computational studies, 6,12,15,21,27,47,48 while corresponding experimental values are in the range of 200-600 mV. [49][50][51][52][53] Addition of NaCl leads to a pronounced change in the electrostatic potential of a PC membrane: The peak of the potential in the region of the lipidwater interface increases and is shifted toward the water phase, reflecting most likely a considerable reorientation of head group dipoles.…”
Section: Resultssupporting
confidence: 91%
“…Considering the plasma membrane of eukaryotic cells, the computational studies that have been carried out by far have focused on the effect of monovalent 6,12,14,15 (NaCl) and divalent 11 (CaCl 2 ) salts on bilayers comprised of zwitterionic PCs. This setup essentially corresponds to the outer leaflet of the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the surface group is more likely to be a phosphate group associated with cations than a choline group associated with anions. This is consistent with previous studies by IR spectroscopy [9] and molecular dynamics simulations [12,30]. These studies have suggested that the metal cations specifically bind to phosphate groups, while chloride anions remain solvated near the surface.…”
Section: Direct Imaging Of Lipid-ion Network Formation Under Physiolosupporting
confidence: 93%
“…[28][29][30][31][32][33][34][35][36][37][38][39][40][41] As for molecular-level computational studies, the increase in computing power in the past few years has made it possible to extend computer simulations beyond the relatively long relaxation times of tens to hundreds of nanoseconds required for equilibration of ions in lipid/water systems. Although most computational studies by far have focused on the effects of salt ions on zwitterionic (neutral) lipid bilayers, 33,[42][43][44][45][46][47][48][49][50][51][52][53] there is also an increasing number of studies on anionic [54][55][56][57][58][59] and cationic 60,61 lipid bilayers. Most simulations have addressed the effect of ions on the structural and electrostatic properties of lipid membranes.…”
Section: Introductionmentioning
confidence: 99%